The Impact of Project-Based Learning Strategies Versus Conventional Strategies, As Well As Students' Interest in Reading, On The Learning Outcomes of Writing Short Stories on Religious Themes Among - Eti Sukowati; Rahmat Kartolo; Sutikno Sutikno (International Journal of Educational Research Excellence (IJERE), 2024)
The aim of this research is (1) to be able to describe the differences in learning outcomes for writing religious short stories between groups of students taught with project-based learning strategies and groups of students taught with conventional strategies. (2) to be able to describe the differences in learning outcomes of writing religious short stories between groups of students who have high interest in reading short stories and students who have low interest in reading and (3) to be able to describe the interaction between project-based learning strategies and interest in reading short stories on ability write a short religious story for class VII students of SMP Negeri 1 Deli Tua for the 2023-2024 academic year. The population in this study was the entire class VII students of SMP Negeri 1 Deli Tua for the 2023-2024 academic year, totaling 160 students. The sample in this study consisted of 2 classes, namely classes VII-1 and VII-2, class VII-1 as the experimental class, and class VII-2 as the control class. The instrument used was a questionnaire and the students' ability to write short stories was a work test. From the results of the research conducted, it can be seen that the mean ability to write short stories in the experimental class was 83.19, while the control class was 72.22; The mean interest of the experimental class was 88.11 while the control class was only 58.44. The conclusion of this research is that there is a difference in learning outcomes for writing religious short stories between the group of students taught with project-based learning strategies and the group of students taught with conventional strategies of 83.1.